Synthesis of Some Metal Complexes with New Heterocyclic Ligand (5-(((2-(3-(1H-indol-3-yl)acryloyl)phenyl)amino)methylene)-2-thiooxodihydropyrimidine-4,6(1H,5H)-dione) and Their Biological Effectiveness as Antioxidant and Anti-Cancer - Hilal, Thanaa Abdul Ameer; Kareem, Ibtihal Kadhim (Universitas Gadjah Mada, 2025)
A novel ligand 5-(((2-(3-(1H-indol-3-yl)acryloyl)phenyl)amino)methylene)-2-thioxodihydropyrimidine-4,6(1H,5H)-dione) (L1) which contains two groups of carbonyl synthesized in one pot and three-component reaction with thiobarbituric acid as starting material, and its complexes with Co(II), Ni(II), Cu(II), Zn(II) and Au(III) have been synthesized. The results of spectrophotometry, nuclear magnetic resonance of proton (H-NMR), infrared spectroscopy (FTIR), ultraviolet and visible (UV-vis) spectroscopy, X-ray diffraction (XRD), elemental analysis (CHNS) and molar conductivity measurements were used to suggest the proposed structures. These data have been utilized to propose appropriate geometric configurations for all complexes. The L1 coordinates toward the metal ions Co(II), Ni(II), Cu(II), and Zn(II), giving an octahedral geometry, while it has a square planar shape with the Au(III) ion. Scanning microscopy (FE-SEM) was used to determine the size of nanoparticles. The present investigation employs a comprehensive molecular docking analysis to assess the binding energies of anti-cancer drugs, thereby elucidating their binding affinity towards the receptor. This indicates that the [Au(L1)Cl]Cl2 complex has a strong affinity for the protein kinase (1HK7). Significant antiproliferative activity was seen in it against human breast cancer (MCF-7) and normal cell lines (MCF-10), as evidenced by the IC50 and selective indices (SI) values. This study could contribute to the development of pharmaceutical preparations.